APLIKASI INOVASI HIJAU DI UMK RUMAH MOCAF, INDONESIA - Ai Indriani; Euis Yunita Purnama Sari; Bismantara (Seminar Nasional Pariwisata dan Kewirausahaan (SNPK), 2024)
UMK as business actors who produce various necessities of life, are one of the contributors to the causes of environmental damage. The negative impacts caused by UMK activities start from its efforts to obtain raw materials, production processes, and waste produced both at the time of production and afterward. The implementation of green business is becoming increasingly important after most countries in the world have ratified the Sustainable Development Goals (SDGs). With a target of 160 points, the SDGs seek to save the earth, human population and increase prosperity that will be achieved by 2030. One of the UMK that has implemented Green Innovation on products and their manufacturing process is Rumah Mocaf Indonesia, Rumah Mocaf Indonesia is a UMK that sells products made from cassava. These raw materials are the crops of local cassava farmers, so we also contribute to the welfare of farmers. Sustainable Business is a Company's ability to achieve business goals and increase long-term value for shareholders by integrating economic, social and environmental into its business strategy. Green Innovation is known as sustainable innovation, which is a process by which sustainability considerations such as environmental, social finance are integrated into the company's system from the idea stage through research and development (R &D) and commercialism. Sustainability processes impact products, services, technology, and new business and organizational models. Green Product Innovation helps companies to gain a competitive advantage by distinguishing their products from competitors who do not do green product innovation (Reinhardt, 1998). Based on the results of the analysis, it turns out that Rumah Mocaf Indonesia UMK in creating a competitive advantage for products are influenced by green product innovation. Green Product Innovation affects the competitive advantage of products and marketing performance at Rumah Mocaf Indonesia UMK. Meanwhile, the influence of Green Process Innovation on Product Competitive Advantage and Marketing Performance of Green Process Innovation affects the competitive advantage of products at Mocaf Indonesia House UMK. Green process innovation is also known as the innovation process which is an environmentally friendly composition of one or more innovation processes (for example, water recycling desulfurized gas fuel).